Noise-induced tinnitus: auditory evoked potential in symptomatic and asymptomatic patients (Clinics, 2014)
OBJECTIVES: We evaluated the central auditory pathways in workers with noise-induced tinnitus with normal hearing thresholds, compared the auditory brainstem response results in groups with and without tinnitus and correlated the tinnitus location to the auditory brainstem response findings in individuals with a history of occupational noise exposure. METHOD: Sixty individuals participated in the study and the following procedures were performed: anamnesis, immittance measures, pure-tone air conduction thresholds at all frequencies between 0.25-8 kHz and auditory brainstem response. RESULTS: The mean auditory brainstem response latencies were lower in the Control group than in the Tinnitus group, but no significant differences between the groups were observed. Qualitative analysis showed more alterations in the lower brainstem in the Tinnitus group. The strongest relationship between tinnitus location and auditory brainstem response alterations was detected in individuals with bilateral tinnitus and bilateral auditory brainstem response alterations compared with patients with unilateral alterations. CONCLUSION: Our findings suggest the occurrence of a possible dysfunction in the central auditory nervous system (brainstem) in individuals with noise-induced tinnitus and a normal hearing threshold.